IMPLEMENTASI PROGRAM CIPTA KARYA SESUAI (BAKAT MINAT) DALAM MEMBANGUN KREATIVITAS DAN KONSISTENSI SISWA DI SEKOLAH DASAR - Varianta Java Yuam Miranda; Muhammad Hanief; Ika Ratih Sulistiani (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
The reasearch that has been carried out is the latest finding entitled”Implementation of the appropriate work creation program (interest talent) in building creativity and student consistency at the Bani Hasyim Singosari Islamic Elementary School Malang”.(1) This study discusses the planning, implementation and evaluation of the creative work program according to talent and interest in building creativity and student consistency (2) The object of the research is at the Bani Hasyim Singosari Islamic Elementary School Malang, which is the only international standard elementary school that holds the program copyright of works(3) The method used is descriptive qualitative by means of data collection, data reduction and drawing conclusions (4) The results of the reaserch provide findings on the stages of the creation program plan, application in low and high class,objectives, benefits, and evaluation of the program.